Wakefield excitation in plasma by ramped sequence of ramped electron bunches - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2012)
It has been shown that wakefield in the regions, occupied by bunches-drivers, does not depend on a longitudinal coordinate for certain lengths of bunches, distance between bunches and the charge is ramped by linear law. For increase of number of accelerated electrons long sequence of electron bunches-drivers, charge of which is distributed according to linear law along each bunch, providing large transformation ratio and homogeneous wakefield, which enable to completely decelerate bunches-drivers, has been constructed.